Analisis Produktivitas Kerja Pegawai Dalam Meningkatkan Pelayanan Prima di Bagian Sumber Daya Manusia Rumah Sakit Umum Pusat Dr. Sardjito - Esa Septian (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This study aims to analyze the level of employee productivity in the Human Resources Section of the Central General Hospital (RSUP) Dr. Sardjito in improving excellent service to the community. The type of research used in this research is descriptive qualitative with a case study approach. Data collection techniques through interviews, observation, and documentation. Data analysis uses the Miles and Huberman model through data reduction, data presentation, and conclusion drawing. The results of this study indicate that the quantity of work shows that the workload that has been assigned to employees in the HR Department is still uneven between employees. The quality of work produced in the form of output has not been optimal in the delegation of authority. In terms of timeliness, it is by the main tasks and functions of each but the additional workload makes the resulting output less than optimal. Factors affecting employee work productivity include a motivating mental attitude, competent employees, production facilities, technology utilization, and career paths.